Entitlement in Gutting's Epistemology of Philosophy: Comments on What Philosophers Know. Issue 1 (1st March 2013) - Henderson, David
Abstract In What Philosophers Know, Gary Gutting provides an epistemology of philosophical reflection. This paper focuses on the roles that various intuitive inputs are said to play in philosophical thought. Gutting argues that philosophers are defeasibly entitled to believe some of these, prior to the outcome of the philosophical reflection, and that they then rightly serve as significant (again defeasible) anchors on reflection. This paper develops a view of epistemic entitlement and applies it to argue that many prephilosophical convictions of the kind Gutting discusses would be just the sort of belief for which entitlement would plausibly be defeated from the start. They then could not properly play the role in philosophical reflection that Gutting envisions for them.